Theoretical approaches to human smuggling - Theodore Baird (Danish Institute for International Studies (DIIS), 2013)
Human smuggling is a global phenomenon which has been difficult to research. Even though there is a large and growing literature on human smuggling, the literature lacks a systematic review of the major theoretical and conceptual approaches. This literature review is organized with the purpose of clarifying and understanding the diversity of theoretical approaches used in the study of migrant smuggling. Six separate theoretical approaches are identified and discussed: 1) organizational or network approaches, partially based on criminological models; 2) mode of crossing and likelihood of capture models, including estimations of migration rates and flows; 3) migration industry and market approaches; 4) global historical comparisons; 5) human rights responses which are concerned with legal arguments; and 6) gender approaches. The review concludes with suggestions for future research.
Keywords: 300